Analisa Prediksi Aliran Sungai Indragiri Menggunakan Model GR3J (Genie Rural a 3 Parametres Journalie) - Mifta Khairiah; Manyuk Fauzi; Imam Suprayogi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Development of water resources in the Indonesian Provinces of Riau in particular require a simplification in the form of a model is needed to transform rain into rate of flow.This study examines the rainfall-runoff modeling methods GR3J on Indragiri watershed. In this modeling input data including the data used daily rainfall and potential evapotranspiration data is that the results are calibrat edusing discharge data daily observations. In this modeling sought optimum value of the parameter modeling GR3J which produces deviation or the smallest error. There are two stages in this model, namely: Model calibration and verification flow model based on the data recording station Lubuk Ambacang guess water for 10 years( 1995-2004). To calculate the deviation thatoccursis used method of Nash-Sutcliffe Coefficient. This modeling to optimize four free parameters such as Maximum Capacity Production Store(XI), Coefficient Changes in Groundwater (X2) and the unit hydrograph (X3). The results of this study concluded that the model can represent from DAS GR3J Indragiriby obtaining the value of the text sarevery good at this stage ofthe model calibration and verification phase. Pasacalibration phase texts most excellent value that thes cheme 9 at 36.89. And at theverification stage nash value and the value ofthe greatest correlation coefficientis also shown in the schematic 9 of 0.77% and acorrelation coefficientof 0.61%..Key Word : Indragiri, Rain-Flow, model GR3J.